Challenges faced by communities moving away from Chhaupadi in Far-Western Nepal - Wong, Fiona Gui Xiang (Kathmandu School of Law Review, 2018)
Chhaupadi is the practice of menstrual hut seclusion in the Far- and Mid-western regions of Nepal that also prescribes a slew of other menstrual restrictions and taboos that constitute human rights violations. Although both the government of Nepal and activists has worked to make Bedkot municipality in Kanchanpur district a Chhaupadi-free municipality, it is unclear what challenges the community has faced as a result of these efforts. This case study used semi-structured interviews with the residents of Ward 1 and 2 of Bedkot municipality to find out what challenges have been faced by those directly affected by anti-Chhaupadi efforts. The findings of this study reveal that Chhaupadi-eradication efforts resulted in emotional distress, loss of property, and social discontent among the residents of these Wards. This study concludes that resorting to “quick fixes” to eradicate deeply-rooted cultural malpractices like Chhaupadi brings about significant harm and dissatisfaction among the affected population. To better bring about sustainable change within communities would thus require concerted and persistent efforts from all parties and stakeholders involved.DOI: https://doi.org/10.46985/jms.v6i2.206